THE CONCEPT OF MUTAKALLIMIN IN THE INTERPRETATION OF DILALAH AL-LAFA AND ITS IMPLICATIONS IN IKHTILAF FIKH - Nurdin, Muhammad Saddam; Haddade, Abd. Wahid; Santalia, Indo (International Journal of Islamic Studies, 2022)
This research is related to the concept or method of the scholars’ mutakallimin through the study of manṭūq (expressed) and mafhūm (implied) by which the technique of interpreting and to interpret the existing of divine revelation texts with a study called dilālah al-lafaẓ and its implications on ikhtilāf fiqh. Understanding of a text of the Koran and the hadiths of the Prophet. sometimes based on the sound of words that are manq both explicitly and containing other possible meanings, and sometimes based on understanding the meaning of mafhūm. This type of research refers to qualitative research in the form of library research. So that this research has benefits and in-depth goals which will later provide a concept of understanding related to the concept of mutakallimīn in interpreting the existing arguments and what their implications are for masāilkhilāfiyah. The results show that the concept of mutakallimn in interpreting the propositions in the text is based on a logical, theoretical approach that is strengthened by evidence and among them are scholars of the Shafi'i, Maliki, Hanbali schools and kalam scholars from Mu'tazilah and Asya'irah.